Healthy elderly and influenza vaccination - Marianne J. Heins; Mariëtte Hooiveld; Joke C. Korevaar (Taylor & Francis Group, 2018)
In many countries, those at risk for complications due to influenza are invited for influenza vaccination, to prevent serious consequences for themselves and those around them. However, vaccination rates are decreasing. The first invitation for vaccination may provide an opportunity to convey ample information about the (dis)advantages of vaccination. We aimed to identify subgroups less likely to be vaccinated after their first invitation. Using data from 87 general practices participating in NIVEL Primary Care Database, we selected persons invited for vaccination for the first time because of their 60th birthday. Of 3.238 included persons, 78% were not vaccinated after their first invitation and in the vast majority (84%) this decision remained consistent over the next years. Men and those with fewer GP contacts were less likely to be vaccinated. This latter group is not easily reached by the GP, so maybe other ways should be considered to convey information about influenza vaccination.